ANALISIS FAKTOR PENYEBAB TERHADAP SALAH SATU PIHAK YANG MELAKUKAN KASUS INGKAR JANJI MENIKAH (STUDI KASUS PADA RUMAH PEREMPUAN KUPANG) - Simon, Mario Stanic; Usman, Siti Ramlah; Dinata, Husni Kusuma (Petitum Law Journal, 2023)
Marriage is the behavior of creatures created by God Almighty so that life in the natural world can reproduce. Regarding marriage, it is regulated in Articles 26 to 102 of the Civil Code, where the general provisions in the Civil Code are contained in Article 26 of the Civil Code which reads: